Implementasi Teknologi Aztec Code Pada Desain Sistem Reservasi Tiket Bus Berbasis Android - Rismayani, Rismayani; Nurani; Pineng, Martina; Patasik, Madyana; Sambo Layuk, Novita (LPPM Universitas Potensi Utama, 2023)
This research aims to apply the Aztec Code technology to design an Android-based inter-district bus ticket reservation system in South Sulawesi. So far, bus ticket reservations are still made via telephone and even come directly to bus representatives, and the tickets given are still in conventional form. The method used in the implementation uses the Aztec Code, where the Aztec Code will be obtained in digital bus tickets or printed form. Aztec Code is a code that can store alphanumeric information that can be scanned, which makes the Aztec Code easier to read in the scanning process. Furthermore, an Android-based platform is used for smartphone devices in building the system. The result of the research is to design a system that can be used in making bus ticket reservations that are applied to Bintang Prima Makassar, which uses Aztec Code technology and has a good level of ease of reading when scanning the code. Based on the functional testing of the system, valid data is generated.